Jasmonate-induced defenses: A tale of intelligence, collaborators and rascals - Ballare, Carlos Luis (2011)
Plants have sophisticated defense systems to protect their tissues against the attack of herbivorous organisms. Many of these defenses are orchestrated by the oxylipin jasmonate. A growing body of evidence indicates that the expression of jasmonate-induced responses is tightly regulated by the ecological context of the plant. Ecological information is provided by molecular signals that indicate the nature of the attacker, the value of the attacked organs, phytochrome status and thereby proximity of competing plants, association with beneficial organisms and history of plant interactions with pathogens and herbivores. This review discusses recent advances in this field and highlights the need to map the activities of informational modulators to specific control points within our emerging model of jasmonate signaling.